Pengembangan Sistem Instruksional Untuk Meningkatkan Kualitas Pembelajaran di Yayasan Perguruan At-Taufiq SD Swasta - Maulidayani Maulidayani; Mela Safitri Situmorang; Fauzan Azhimah; Syafitri Halawa; Salwa Nabila Damanik (SOKO GURU: Jurnal Ilmu Pendidikan, 2023)
The aim of this research is to explain the development of an instructional system to improve the quality of learning in private elementary schools or elementary schools, The method used in this research is a descriptive research method using qualitative. Data was obtained from interviews, observation and documentation. The development of an instructional system to improve the quality of learning aims to develop an innovative learning system to improve the quality of learning in the school environment. The development methods used include needs analysis, system design, implementation, evaluation and continuous revision. This system is designed to support teacher and student interaction, facilitate technology-based learning, and provide fast feedback. By integrating technology, this system is expected to increase student engagement, improve understanding of concepts, and optimize the teaching and learning process. This research contributes to the development of modern learning models that can increase the effectiveness and efficiency of learning in schools.